Current status and future aspects in the Japan Stroke Data Bank - Wada, Shinichi; Yoshimura, Sohei; Miwa, Kaori; Iwanaga, Yoshitaka; Koga, Masatoshi; Toyoda, Kazunori (Frontiers in Neurology, 2023)
The Japanese National Plan for the Promotion of Measures Against Cerebrovascular and Cardiovascular Diseases was formulated on October 27, 2020. One purpose of this plan was to promote research on cerebrovascular and cardiovascular diseases. Therefore, it is necessary to clarify the actual status of stroke treatment in Japan and operate a national stroke database with high public interest completely and accurately. The Japan Stroke Data Bank (JSDB; https://strokedatabank.ncvc.go.jp/en/) was established by the Ministry of Health, Labor and Welfare Scientific Research in Shimane University (Shimane, Japan) in 1999 and was transferred to the National Cerebral and Cardiovascular Center (Osaka, Japan) as a part of the Cardiovascular Disease Registry in 2015. More than 200,000 of stroke cases have been registered using individual forms from more than 100 nationwide stroke centers over ~20 years. Since there are few large-scale stroke registries with nationwide coverage in Asia, including Japan, compared with those in Europe and North America, the role of the JSDB in the plan will be important in the future. To construct a high-quality stroke registry, we aimed to (1) collect detailed data through individual questionnaires for each participating stroke center, (2) link to external databases (e.g., insurance claims and public death registries), (3) improve the quality of treatment at participating hospitals through benchmarking, and (4) obtain stable funding through sustained support from government and academic societies. We also describe the history of the JSDB and changes in the trend of real-world stroke treatment in Japan based on the results of analysis of data in the JSDB.